2008
DOI: 10.1088/0953-8984/20/47/475202
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of mechanically milled ZnO: influence of zirconia milling media

Abstract: Zinc oxide nanoparticles were obtained by milling in a planetary ball mill with a zirconia milling assembly for up to 5 h in air. The samples were characterized by scanning electron microscopy, x-ray diffraction (XRD) and Raman spectroscopy methods. The deviation of the lattice parameters from single crystal values was related to defect creation and increase of strain inside the hexagonal lattice of milled ZnO nanoparticles. The observed redshift and peak broadening of the major first-order Raman modes were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…The mode at ∼960 cm −1 can be assigned to an overtone in the Raman spectrum of monoclinic ZrO 2 , [27] whereas the features at about 1003, 1067, 1078 and 1093 cm −1 are previously noticed in the Raman spectra of sintered samples prepared from the ZnO powders obtained by milling in zirconia vials. [28] These higher order Raman modes related to ZrO 2 introduced in ZnO powder by prolongated milling in zirconia vials are enhanced under the resonant condition. Such resonant enhancement arises because of vicinity of the laser excitation energy (2.41 eV) to the energy of some electronic transitions related to the mid-gap states, such as surface states and oxygen vacancies in ZrO 2 .…”
Section: Raman Scatteringmentioning
confidence: 95%
See 1 more Smart Citation
“…The mode at ∼960 cm −1 can be assigned to an overtone in the Raman spectrum of monoclinic ZrO 2 , [27] whereas the features at about 1003, 1067, 1078 and 1093 cm −1 are previously noticed in the Raman spectra of sintered samples prepared from the ZnO powders obtained by milling in zirconia vials. [28] These higher order Raman modes related to ZrO 2 introduced in ZnO powder by prolongated milling in zirconia vials are enhanced under the resonant condition. Such resonant enhancement arises because of vicinity of the laser excitation energy (2.41 eV) to the energy of some electronic transitions related to the mid-gap states, such as surface states and oxygen vacancies in ZrO 2 .…”
Section: Raman Scatteringmentioning
confidence: 95%
“…Such resonant enhancement arises because of vicinity of the laser excitation energy (2.41 eV) to the energy of some electronic transitions related to the mid-gap states, such as surface states and oxygen vacancies in ZrO 2 . [28,29] …”
Section: Raman Scatteringmentioning
confidence: 99%
“…They reported that the absorbance of UV light increased with decreasing particle size and the particle size increased with an increasing calcination temperature. Vojisavljevic et al [11] investigated the preparation of ZnO nanoparticles by milling at 400 rpm, the ball to powder ratio (BPR) was 40:1 and milling time was 30, 90 and 300 min. From this study, the XRD peak positions were shifted to a higher angle and the intrinsic defect concentration increased with increased milling time.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical activation of ZnO powder causes a decrease in the intensity of Raman spectra as well as redshift of some Raman modes attributed to the formation of intrinsic defects by mechanical activation of ZnO (Šćepanović et al, 2006). The redshift (∼2-8 cm −1 ) and peak broadening are consequences of the intrinsic defect formation by mechanical milling, combined with confinement size effects (Vojisavljević et al, 2008). The combined action of recrystallization and formation of lattice defects in the wet super-fine system and crystal size and lattice deformation of ZnO presented fluctuating changes, leading to reduction of Zn-O bond stretching vibrational frequency and decrease in wavenumbers of absorption peak.…”
Section: Surface Groups Analysesmentioning
confidence: 99%